1174 The Reporting of Centre and Surgeon Experience in Studies of Robot Assisted Cholecystectomy: A Systematic Review. (12th October 2021) - Ramirez, J; Jones, C; Leow, T W; Rozwadowski, S; Wijeyaratne, M; Jones, A; Hoffman, C; Kirkham, E; ,
Abstract: Introduction: Over 90% of cholecystectomies are performed using minimally invasive techniques. Robotic cholecystectomy (RC) has been developed to overcome technical limitations of laparoscopy, including improved range of movement and visualisation. Despite becoming increasingly widespread, the safety and efficacy of RC remain unestablished. This review aims to analyse the quality assurance reporting through centre and surgeon expertise in RC. Method: A systematic search was conducted to identify all published studies reporting RC. Data on quality assurance measures were collected, including: centres involved, surgeons' experience and training. Results: Of the 1425 abstracts screened, 90 full-text papers were included. Sixty-four studies (71%) were single institutions. Of the thirty studies (33%) reporting centre type, 28 were conducted in specialist/regional/tertiary centres. Only four stated their caseload of RC. No studies described pre-specified criteria or minimum experience required for a surgeon to participate. Fifty-two (58%) reported the number of surgeons operating and 13 (14%) stated surgeons' training grade. Two quantified previous RC experience, 7 stated prior laparoscopic experience. Only 21 (23%) described training prior to the surgeons' first in-human procedure; animal based (n = 12), simulation (n = 12), observation (n = 4), lab-based (n = 3). Specific mentorship was reported in 8 studies, and 13 described dual operating. Conclusions: Little information was provided about the experience and training of operating surgeons, making it difficult to ascertain whether replicable techniques were utilised which would allow development of a learning curve. This highlights the need for better transparency when reporting surgical innovation, to ensure the safe, evidence-based adoption of new technologies into clinical practice.